Packing material for power storage device and power storage device using same
By using the reaction products of acid-modified polyolefins and polyfunctional isocyanate compounds and anti-corrosion treatment layer in the packaging materials of lithium-ion batteries, the problem of insufficient heat resistance and moisture barrier in high temperature environments is solved, and the full solid state is significantly improved Battery sealing and performance stability.
Patent Information
- Application Number
- CN202380039646.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-30
- Filing Date
- 2023-05-23
- Publication Date
- 2024-12-20
AI Technical Summary
The packaging materials of existing lithium-ion batteries are insufficient in high temperature environments, resulting in a reduction in sealing properties of all-solid batteries, and it is difficult to take into account both the heat resistance and moisture barrier properties of commonly used adhesives.
Using a second adhesive layer with the reaction product of acid-modified polyolefin and polyfunctional isocyanate compound, the urethane bond and crosslinking structure are adjusted by infrared spectroscopy to improve the adhesion and heat resistance between the metal foil layer and the sealing layer. and a corrosion-proof treatment layer and hydrogen sulfide adsorption substance are added to the first and second adhesive layers to enhance the heat resistance and moisture barrier properties of the encapsulation material.
It has achieved significant improvement in the heat resistance and moisture barrier properties of the packaging materials under high temperature environments, ensuring stable sealing and performance of all-solid-state batteries, and is suitable for lithium-ion batteries under high temperature conditions.
Smart Images

Figure CN119174034A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a packaging material for an electric storage device and an electric storage device using the packaging material for an electric storage device. Background Art
[0002] As a power storage device, it is known that there are secondary batteries such as (for example) lithium ion batteries, nickel-metal hydride batteries and lead storage batteries, and electrochemical capacitors such as double-layer capacitors. Due to the miniaturization of portable devices or the limitation of the installation space, it is required that the power storage device be further miniaturized, so lithium ion batteries with high energy density have attracted much attention. As the packaging material used for lithium ion batteries, multilayer films that are light in weight, high in heat dissipation and can be made at low cost are gradually used.
[0003] A lithium-ion battery using the multilayer film as a packaging material is called a laminated lithium-ion battery. By covering the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) with the packaging material, moisture is prevented from entering the interior. A laminated lithium-ion battery can be manufactured, for example, by forming a recess in a portion of the packaging material by cold forming, accommodating the battery contents in the recess, and folding back the remaining portion of the packaging material and sealing the edge portion by heat sealing (for example, refer to Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-101765 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, as the next generation battery of lithium-ion batteries, research and development of power storage devices called all-solid-state batteries are underway. All-solid-state batteries have the characteristics of using solid electrolytes as electrolytes instead of organic electrolytes. Lithium-ion batteries cannot be used at temperatures higher than the boiling point of the electrolyte (about 80°C), while all-solid-state batteries can be used at temperatures exceeding 100°C and can improve the conductivity of lithium ions by operating at high temperature conditions (e.g., 100-150°C).
[0009] However, when a laminated all-solid-state battery is manufactured using the multilayer film as a packaging material, if the heat resistance of the packaging material is insufficient, the interlayer adhesion in a high temperature environment cannot be ensured, the lamination strength is reduced, and the sealing of the package of the all-solid-state battery may be reduced. The packaging material, for example, has a structure in which a base material layer, a metal foil layer, and a sealing layer are stacked via an adhesive layer, but the adhesion between the metal foil layer and the sealing layer is easily reduced in a high temperature environment.
[0010] In addition, the sulfide-based solid electrolytes used in all-solid-state batteries sometimes react with moisture in the atmosphere to produce hydrogen sulfide gas, which reduces the performance of the battery. As the adhesive used on the inner layer side, urethane adhesives or epoxy adhesives, which are generally heat-resistant adhesives, can be listed. However, the moisture barrier properties of these adhesives are insufficient. In addition, as adhesives with high moisture barrier properties, for example, acid-modified polyolefin-based adhesives can be listed. However, the heat resistance of these adhesives is insufficient. In this way, the heat resistance and moisture barrier properties of the adhesive become a tradeoff. Moreover, in the packaging materials used in all-solid-state batteries, it is required to have excellent moisture barrier properties even in high temperature environments.
[0011] One aspect of the present disclosure provides a packaging material having excellent heat resistance and excellent moisture barrier properties even under a high temperature environment.
[0012] Means for solving problems
[0013] One aspect of the present disclosure is a packaging material for a power storage device, the packaging material having a laminated structure including a substrate layer, a first adhesive layer, a metal foil layer, a second adhesive layer, and a sealing layer in this order, wherein the second adhesive layer contains at least a reaction product of an acid-modified polyolefin and a polyfunctional isocyanate compound, and the second adhesive layer satisfies the condition represented by the following inequality (1):
[0014] 0.01≤{(C+D)-B} / A≤0.60…(1)
[0015] [wherein, A to D are the intensities of the infrared absorption spectrum of the second adhesive layer measured by infrared spectroscopy, and A represents the wave number 3040 to 2760 cm -1 The maximum intensity, B represents the wave number 1850~1780cm -1 The maximum intensity, C represents the wave number 1760~1600cm -1 The maximum intensity, D represents the wave number 2150~2090cm -1 Maximum strength.]
[0016] The above-mentioned packaging material has excellent heat resistance and moisture barrier properties. The inventors consider the following reasons for producing such an effect. That is, the reaction product of the acid-modified polyolefin and the multifunctional isocyanate compound contained in the second adhesive layer has a carbamate bond. Since the carbamate bond is a polar group, the adhesion between the second adhesive layer and the metal foil layer is improved. In addition, the reaction product of the acid-modified polyolefin and the multifunctional isocyanate compound has a cross-linked structure produced by the reaction of the carboxylic acid in the acid-modified polyolefin and the multifunctional isocyanate compound. Therefore, the heat resistance of the second adhesive layer itself is also improved.
[0017] In addition, when using ordinary acid-modified polyolefins, the entanglement of the molecular chains of the acid-modified polyolefins is eliminated under high temperature conditions due to the low glass transition temperature. Therefore, the gap between molecules becomes wider and the moisture barrier property of the packaging material decreases. On the other hand, when using the reaction product of the acid-modified polyolefin and the multifunctional isocyanate compound, a cross-linked structure based on the multifunctional isocyanate compound is constructed between multiple acid-modified polyolefin molecules. Therefore, the glass transition temperature becomes high and the entanglement of the molecular chains is difficult to eliminate.
[0018] In the second adhesive layer, the infrared absorption peak measured by infrared spectroscopy is specified to be 0.01 or more and 0.60 or less. A represents the wave number 3040 to 2760 cm-1 of the olefin structure derived from the above reaction product. -1 The maximum intensity of B represents the wave number 1850-1780 cm-1 from the maleic anhydride structure of the above reaction product. -1 The maximum intensity of C represents the wave number of 1760-1600 cm-1 of the urethane bond from the above reaction product. -1 The maximum intensity of D is from the wave number 2150-2090cm-1 of the carbodiimide compound. -1 By making the above X be 0.01 or more, the second adhesive layer has sufficient urethane bonds. As a result, the interlayer adhesion and the heat resistance of the second adhesive layer itself become excellent. In addition, by making the above X be 0.60 or less, the affinity of the second adhesive layer with water molecules can be suppressed, and the gap between molecules can be suppressed by the cross-linked structure. As a result, the heat resistance and moisture barrier properties of the packaging material become excellent. In addition, the hydrogen sulfide resistance of the packaging material is also excellent.
[0019] In one embodiment, at least one of the groups consisting of a polymer of aliphatic polyfunctional isocyanate compounds and a polymer of a polyfunctional isocyanate compound containing an aromatic ring may be included. In the case where the polyfunctional isocyanate compound is a polymer of aliphatic polyfunctional isocyanate compounds, compared with the case of larger isocyanate compounds such as polymers of isophorone diisocyanate, the gap between molecules constructed by cross-linking reaction becomes smaller. Therefore, the moisture barrier of the encapsulating material is more excellent. In addition, in the case where the polyfunctional isocyanate compound is a polymer of a polyfunctional isocyanate compound containing an aromatic ring, due to the interaction (π-π stacking) of the aromatic rings, the distance between molecules narrows. Therefore, the moisture barrier of the encapsulating material tends to be more excellent.
[0020] In one embodiment, the packaging material may include an anti-corrosion treatment layer between the first adhesive layer and the metal foil layer, or between the second adhesive layer and the metal foil layer, or both. The packaging material includes an anti-corrosion treatment layer, and the adhesion between the adhesive layer provided with the anti-corrosion treatment layer and the metal foil layer is improved. Thus, the heat resistance of the packaging material tends to be more excellent. In addition, the anti-corrosion treatment layer is used to impart hydrogen sulfide resistance to the packaging material. Thus, even after exposure to hydrogen sulfide, the heat resistance of the packaging material tends to be excellent.
[0021] In one embodiment, the sealing layer may include at least one of a polyolefin resin and a polyester resin. These resins have a higher melting point than, for example, an acrylic resin, and have good compatibility with the second adhesive layer comprising a reaction product of an acid-modified polyolefin and a multifunctional isocyanate compound, and have excellent adhesion. In addition, the softness of these resins is, for example, better than that of an acrylic resin. In addition, the affinity with water molecules is, for example, lower than that of an acrylic resin. Therefore, the heat resistance and moisture barrier properties of the encapsulating material tend to be more excellent.
[0022] In one embodiment, at least one of the first adhesive layer and the second adhesive layer may contain a hydrogen sulfide adsorbing substance. Thus, the heat-resistant lamination strength of the packaging material tends to be more excellent even after exposure to hydrogen sulfide.
[0023] In one embodiment, the second adhesive layer may further include a carbodiimide compound. As a result, the heat resistance of the packaging material tends to be more excellent. The inventors speculate that the reason for this effect is that the carbodiimide group with high polarity forms a hydrogen bond with other polar groups in the metal foil layer or the second adhesive layer.
[0024] The above-mentioned packaging material can be used for all-solid-state batteries.
[0025] Another aspect of the present disclosure is an electric storage device comprising: an electric storage device body, a current output terminal extending from the electric storage device body, and the above-mentioned packaging material that clamps the current output terminal and accommodates the electric storage device body. The above-mentioned electric storage device may be an all-solid-state battery.
[0026] Effects of the Invention
[0027] According to one aspect of the present disclosure, there is provided a packaging material that is excellent in heat resistance and excellent in moisture barrier properties even under a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] [ Figure 1 ] Figure 1 This is a schematic cross-sectional view of a packaging material for a power storage device according to one embodiment of the present disclosure.
[0029] [ Figure 2 ] Figure 2This is a schematic diagram showing an example of the infrared absorption spectrum of the second adhesive layer measured by infrared spectroscopy.
[0030] [ Figure 3 ] Figure 3 This is a perspective view of a power storage device according to one embodiment of the present disclosure. DETAILED DESCRIPTION
[0031] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with appropriate reference to the accompanying drawings. It should be noted that in the accompanying drawings, the same or equivalent parts are marked with the same symbols, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.
[0032] [Electricity storage device packaging materials]
[0033] Figure 1 2 is a cross-sectional view schematically showing an embodiment of a packaging material for a power storage device of the present invention. Figure 1 As shown, the packaging material (packaging material for power storage device) 10 of the present embodiment is a laminated body obtained by stacking the following layers: a base layer 11, a first adhesive layer 12 provided on one side of the base layer 11, a metal foil layer 13 provided on the opposite side of the first adhesive layer 12 to the base layer 11 and having anti-corrosion treatment layers 14a and 14b on both sides, a second adhesive layer 15 provided on the opposite side of the metal foil layer 13 to the first adhesive layer 12, and a sealing layer 16 provided on the opposite side of the second adhesive layer 15 to the metal foil layer 13. Here, the anti-corrosion treatment layer 14a is provided on the surface of the metal foil layer 13 on the first adhesive layer 12 side, and the anti-corrosion treatment layer 14b is provided on the surface of the metal foil layer 13 on the second adhesive layer 15 side. In the packaging material 10, the base layer 11 is the outermost layer, and the sealing layer 16 is the innermost layer. That is, the packaging material 10 is used with the base layer 11 facing the outside of the power storage device and the sealing layer 16 facing the inside of the power storage device. Each layer is described below.
[0034] <Base material layer 11>
[0035] The base material layer 11 plays the following roles: imparting heat resistance in the sealing process when manufacturing the power storage device, and suppressing pinholes that may be generated during molding or circulation. In particular, in the case of packaging materials for large-scale power storage devices, it can also impart scratch resistance, chemical resistance, insulation, etc.
[0036] The melting peak temperature of the substrate layer 11 is preferably higher than the melting peak temperature of the sealing layer 16. By making the melting peak temperature of the substrate layer 11 higher than the melting peak temperature of the sealing layer 16, the appearance deterioration caused by the melting of the substrate layer 11 (the outer layer) during heat sealing can be suppressed. In the case where the sealing layer 16 is a multilayer structure, the melting peak temperature of the sealing layer 16 refers to the melting peak temperature of the layer with the highest melting peak temperature. The melting peak temperature of the substrate layer 11 is preferably above 290°C, more preferably 290 to 350°C. As resin films that can be used as the substrate layer 11 and have a melting peak temperature within the above range, there can be listed: nylon film, PET film, polyamide film, polyphenylene sulfide film (PPS film), polyimide film, polyester film, etc. The melting peak temperature refers to the value obtained according to the method described in JIS K7121-1987.
[0037] As the substrate layer 11, a commercially available film can be used, or the substrate layer 11 can be formed by coating (coating and drying of a coating liquid). It should be noted that the substrate layer 11 can be a single-layer structure or a multi-layer structure, or can be formed by coating a thermosetting resin. In addition, the substrate layer 11 can contain various additives (for example, flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, tackifiers, etc.).
[0038] The melting peak temperature T of the base material layer 11 11 The melting peak temperature T of the sealing layer 16 16 The difference (T 11 -T 16 ) is preferably 20° C. or more. By setting the temperature difference to 20° C. or more, deterioration of the appearance of the packaging material 10 due to heat sealing can be further sufficiently suppressed. The thickness of the base material layer 11 is preferably 5 to 50 μm, more preferably 12 to 30 μm.
[0039] <First Adhesive Layer 12>
[0040] The first adhesive layer 12 is a layer that bonds the metal foil layer 13 provided with the anti-corrosion treatment layer 14a to the base layer 11. The first adhesive layer 12 has the adhesive force required to firmly bond the base layer 11 to the metal foil layer 13, and also has the followability to suppress the metal foil layer 13 from being broken by the base layer 11 during molding. It should be noted that the followability is a property that the first adhesive layer 12 does not peel off but remains on the component even if the component is deformed due to expansion and contraction, etc.
[0041] As the adhesive component forming the first adhesive layer 12, for example, there can be listed: carbamate compounds, urea compounds, epoxy compounds, silicone compounds, and inorganic oxides such as aluminum oxide and silicon dioxide. These compounds can be used alone or in combination of two or more. Urea compounds are obtained by reacting amine compounds and amine derivatives with polyfunctional isocyanate compounds. Carbamate compounds are obtained by reacting polyol resins with polyfunctional isocyanate compounds.
[0042] Amine compounds are compounds having an amino group in the molecule. Here, amino group refers to -NH2, -NHR, -NR2. Here, R represents an alkyl group and an aryl group. Amine derivatives are compounds derived from amine compounds and do not have an amino group in the molecule.
[0043] Amine compounds and amine derivatives can be explicit curing agents or latent curing agents. Latent curing agents are curing agents that are activated by external stimuli to generate reactive groups that can react with isocyanate groups. In the case where amine compounds and amine derivatives are latent curing agents, the pot life tends to increase. As external stimuli, for example, heat and moisture can be listed. As latent curing agents, for example, imidazole curing agents, imine curing agents, aminated imide curing agents, dicyandiamide curing agents, aromatic polyamine curing agents, aliphatic polyamine curing agents, polyamide amine curing agents, tertiary amine salt curing agents and oxazolidine curing agents can be listed. Among them, as latent curing agents activated by heating, for example, imidazole curing agents, dicyandiamide curing agents, polyamine curing agents and aminated imide curing agents can be listed. As latent curing agents activated by moisture, for example, imine curing agents and oxazolidine curing agents can be listed. Since the pot life tends to be further improved, the latent curing agent is preferably a latent curing agent activated by moisture.
[0044] Examples of the polyol resin include polyester polyol, polyether polyol, polycarbonate diol, and polyacrylic acid polyol.
[0045] Examples of the polyester polyol include polyester polyols obtained by reacting one or more dicarboxylic acids with a diol.
[0046] Examples of the polyether polyol include polyols produced by addition polymerization of ethylene oxide or propylene oxide with propylene glycol, glycerol, pentaerythritol, and the like.
[0047] Examples of the polycarbonate polyol include polycarbonate polyols obtained by reacting a carbonic acid diester such as diphenyl carbonate with a diol.
[0048] As polyacrylic acid polyol, for example, a copolymer obtained by copolymerizing at least a hydroxyl-containing acrylic acid monomer and (meth)acrylic acid can be cited. In this case, it is preferred to contain a structural unit derived from (meth)acrylic acid as a main component. As hydroxyl-containing acrylic acid monomer, for example, 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate can be cited.
[0049] The polyfunctional isocyanate compound contains a plurality of isocyanate groups and plays a role in cross-linking the above-mentioned amine resin or polyol. The polyfunctional isocyanate compound can be used alone or in combination of two or more. As the polyfunctional isocyanate compound, for example, aliphatic polyfunctional isocyanate compounds, alicyclic polyfunctional isocyanate compounds and polyfunctional isocyanate compounds having aromatic rings can be listed.
[0050] As aliphatic multifunctional isocyanate compounds, for example, hexamethylene diisocyanate (HDI), xylylene diisocyanate (XDI) and the like can be cited. As alicyclic multifunctional isocyanate compounds, isophorone diisocyanate (IPDI) and the like can be cited. As multifunctional isocyanate compounds having an aromatic ring, toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) and the like can be cited. Multifunctional isocyanate compounds can also use polymers (for example, trimers) of these compounds, specifically, adducts, biuret bodies, isocyanurate bodies and the like can be used.
[0051] From the viewpoint of increasing the pot life, the isocyanate group of the polyfunctional isocyanate compound can be bonded to a blocking agent. As the blocking agent, for example, methyl ethyl ketoxime (MEKO) and the like can be cited. The temperature at which the blocking agent is detached from the isocyanate group of the polyfunctional isocyanate compound can be above 50°C, and from the viewpoint of further increasing the pot life, it is preferably above 60°C. The temperature at which the blocking agent is detached from the isocyanate group of the polyfunctional isocyanate compound can be below 140°C, and from the viewpoint of increasing the molding curling resistance of the packaging material, it is preferably below 120°C.
[0052] In order to lower the dissociation temperature of the end-capping agent, a catalyst that lowers the dissociation temperature may be used. Examples of such a catalyst that lowers the dissociation temperature include tertiary amines such as triethylenediamine and N-methylmorpholine, and metal organic acid salts such as dibutyltin dilaurate.
[0053] The first adhesive layer 12 may contain a hydrogen sulfide adsorbing substance so as to be able to suppress corrosion of the metal foil layer 13 caused by hydrogen sulfide present outside the packaging material. Examples of such hydrogen sulfide adsorbing substances include zinc oxide and potassium permanganate. When the first adhesive layer 12 contains a hydrogen sulfide adsorbing substance, the content thereof is preferably 1 to 50% by mass relative to the total amount of the first adhesive layer 12 in order to suppress corrosion of the metal foil layer 13 caused by hydrogen sulfide present outside the packaging material.
[0054] From the viewpoint of obtaining desired adhesive strength, followability, processability, and the like, the thickness of the first adhesive layer 12 is preferably 1 to 10 μm, and more preferably 2 to 6 μm.
[0055] The first adhesive layer 12 can be obtained, for example, by coating a composition containing the above-mentioned components. A known coating method can be used, for example, direct gravure printing, reverse gravure printing (direct, kiss printing), and micro gravure printing.
[0056] The composition may contain a solvent. Examples of such solvents include ethyl acetate, toluene, methyl ethyl ketone, methyl isobutyl ketone, and alcohols. The solvents may be used alone or in combination of two or more.
[0057] <Second Adhesive Layer 15>
[0058] The second adhesive layer 15 is a layer that bonds the metal foil layer 13 and the sealing layer 16 provided with the anti-corrosion treatment layer 14b. The second adhesive layer 15 at least comprises the reaction product of acid-modified polyolefin and polyfunctional isocyanate compound (hereinafter also referred to as "reaction product A"). The components used to obtain reaction product A can be only acid-modified polyolefin and polyfunctional isocyanate compound, or can also contain other components in addition to acid-modified polyolefin and polyfunctional isocyanate compound. As other components, for example, carbodiimide compound, epoxy resin, acrylic resin, silicone resin, silane coupling agent, silica filler, aluminum oxide, zinc oxide, latent curing agent and anti-oxidation degradation agent can be listed. From the perspective that heat resistance and moisture barrier properties tend to be more excellent, reaction product A is preferably at least the reaction product of acid-modified polyolefin, polyfunctional isocyanate compound and carbodiimide compound.
[0059] From the viewpoint of reactivity, the hydroxyl value of the acid-modified polyolefin is preferably 5 to 120 KOHmg / g, more preferably 10 to 80 KOHmg / g, and even more preferably 20 to 60 KOHmg / g.
[0060] Examples of the acid-modified polyolefin include maleic anhydride-modified polyolefins obtained by reacting maleic anhydride with polyolefins. Examples of the maleic anhydride-modified polyolefins include maleic anhydride-modified polypropylene and maleic anhydride-modified polyethylene.
[0061] As the polyfunctional isocyanate compound, the same compound as that of the first adhesive layer can be used. Since the moisture barrier property of the encapsulating material tends to be more excellent, the polyfunctional isocyanate compound is preferably a polymer of an aliphatic polyfunctional isocyanate compound and a polymer of a polyfunctional isocyanate compound containing an aromatic ring.
[0062] From the viewpoint of reactivity, the amount of the polyfunctional isocyanate compound when at least the acid-modified polyolefin and the polyfunctional isocyanate compound are reacted is preferably 0.5 to 40 parts by mass, more preferably 3 to 30 parts by mass, and even more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the acid-modified polyolefin.
[0063] From the viewpoint of heat resistance and adhesion, the amount of the carbodiimide compound when at least the acid-modified polyolefin, the polyfunctional isocyanate compound and the carbodiimide compound are reacted is preferably 0.1 to 10 parts by mass, more preferably 0.3 to 7 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the acid-modified polyolefin.
[0064] The amount of the acid-modified polyolefin blended based on the total amount of the components for obtaining the reaction product A may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more.
[0065] Figure 2 1 is a schematic diagram showing an example of the infrared absorption spectrum of the second adhesive layer 15 measured by infrared spectroscopy. The second adhesive layer 15 satisfies the condition represented by the inequality of the following formula (1).
[0066] 0.01≤{(C+D)-B} / A≤0.60…(1)
[0067] [wherein, A to D are the intensities of the infrared absorption spectrum of the second adhesive layer measured by infrared spectroscopy, and A represents the wave number 3040 to 2760 cm -1 The maximum intensity, B represents the wave number 1850~1780cm -1 The maximum intensity, C represents the wave number 1760~1600cm -1 The maximum intensity, D represents the wave number 2150~2090cm -1 Maximum strength.]
[0068] In view of the tendency to be more excellent in heat resistance, {(C+D)-B} / A is preferably 0.05 or more, more preferably 0.2 or more, and further preferably 0.3 or more. In view of the tendency to be more excellent in moisture barrier properties, {(C+D)-B} / A is preferably 0.5 or less, more preferably 0.45 or less, and further preferably 0.4 or less.
[0069] The infrared absorption spectrum peak intensity can be measured by attenuated total reflection (ATR: Attenuated Total Reflection) of Fourier transform infrared (FT-IR) spectroscopy.
[0070] The second adhesive layer 15 preferably contains a carbodiimide compound because the heat resistance tends to be more excellent. The carbodiimide compound functions as a reaction accelerator and a crosslinking agent for the carboxyl groups contained in the acid-modified polyolefin.
[0071] The second adhesive layer 15 may contain a hydrogen sulfide adsorbing substance similarly to the first adhesive layer. The type and content of the hydrogen sulfide adsorbing substance may be the same as those of the first adhesive layer.
[0072] The thickness of the second adhesive layer 15 is preferably 1 to 5 μm. When the thickness of the second adhesive layer 15 is 1 μm or more, sufficient bonding strength between the metal foil layer 13 and the sealing layer 16 can be easily obtained. When the thickness of the second adhesive layer 15 is 5 μm or less, cracking of the second adhesive layer 15 tends to be suppressed.
[0073] The second adhesive layer 15 is obtained by the same method as the first adhesive layer 12 .
[0074] <Metal foil layer 13>
[0075] The metal foil layer 13 has a water vapor barrier property to prevent moisture from penetrating into the interior of the power storage device. In addition, the metal foil layer 13 may have ductility for deep drawing. As the metal foil layer 13, various metal foils such as aluminum, stainless steel, and copper may be used, for example. These may be used alone or in combination of two or more. As the metal foil layer 13, aluminum foil is preferred from the aspects of mass (specific gravity), moisture resistance, processability, and cost.
[0076] As aluminum foil, from the perspective of being able to impart the desired ductility during molding, it is particularly preferred to use a soft aluminum foil that has been subjected to annealing treatment, but in order to further impart pinhole resistance and ductility during molding, it is more preferred to use an aluminum foil containing iron. In 100% by mass of aluminum foil, the iron content in the aluminum foil is preferably 0.1 to 9.0% by mass, and more preferably 0.5 to 2.0% by mass (for example, aluminum foil made of 8021 material or 8079 material as described in the JIS standard). By making the iron content 0.1% by mass or more, a packaging material 10 having better pinhole resistance and ductility can be obtained. By making the iron content 9.0% by mass or less, a packaging material 10 having better softness can be obtained.
[0077] In order to obtain the desired electrolyte resistance, for example, the metal foil used in the metal foil layer 13 is preferably subjected to a degreasing treatment. In addition, in order to simplify the manufacturing process, as the above-mentioned metal foil, a metal foil whose surface is not etched is preferably used. Among them, for the metal foil used in the metal foil layer 13, in terms of imparting electrolyte resistance, it is preferred to use an aluminum foil that has been subjected to a degreasing treatment. When the aluminum foil is subjected to a degreasing treatment, the degreasing treatment may be applied to only one side of the aluminum foil, or to both sides. As the above-mentioned degreasing treatment, for example, a wet degreasing treatment or a dry degreasing treatment may be used, but from the viewpoint of simplifying the manufacturing process, a dry degreasing treatment is preferred.
[0078] As the dry degreasing treatment, for example, the following method can be cited: in the step of annealing the metal foil, the degreasing treatment is performed by extending the treatment time. Even if the degreasing treatment is performed at the same time as the annealing treatment to soften the metal foil, sufficient electrolyte resistance can be obtained.
[0079] In addition, as the above-mentioned dry degreasing treatment, a treatment other than the above-mentioned annealing treatment, that is, a flame treatment, a corona treatment, etc. can be used. In addition, as the above-mentioned dry degreasing treatment, for example, a degreasing treatment in which active oxygen generated by irradiating ultraviolet rays of a specific wavelength to the metal foil to oxidatively decompose and remove pollutants can be used.
[0080] As the above-mentioned wet degreasing treatment, for example, acid degreasing treatment, alkaline degreasing treatment and the like can be used. As the acid used in the above-mentioned acid degreasing treatment, for example, inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid can be used. These acids can be used alone or in combination of two or more. In addition, as the alkali used in the alkaline degreasing treatment, for example, sodium hydroxide with a high etching effect can be used. In addition, the alkaline degreasing treatment can be carried out using a material combined with a weak alkaline material and a surfactant. The wet degreasing treatment described above can be carried out, for example, by an immersion method or a spraying method.
[0081] From the perspective of barrier properties, pinhole resistance and processability, the thickness of the metal foil layer 13 is preferably 9 to 200 μm, more preferably 15 to 150 μm, and further preferably 15 to 100 μm. By making the thickness of the metal foil layer 13 9 μm or more, it is difficult to break even if stress is applied by molding. By making the thickness of the metal foil layer 13 200 μm or less, the increase in mass of the packaging material can be reduced, thereby suppressing the reduction in the weight energy density of the storage device.
[0082] <Anti-corrosion treatment layers 14a, 14b>
[0083] The anti-corrosion treatment layers 14a and 14b are layers provided on the surface of the metal foil layer 13 to prevent corrosion. In addition, the anti-corrosion treatment layer 14a plays a role in improving the adhesion between the metal foil layer 13 and the first adhesive layer 12. In addition, the anti-corrosion treatment layer 14b plays a role in improving the adhesion between the metal foil layer 13 and the second adhesive layer 15. The anti-corrosion treatment layer 14a and the anti-corrosion treatment layer 14b may be layers of the same composition or layers of different compositions.
[0084] The anti-corrosion treatment layers 14a and 14b can be formed, for example, by subjecting the layer serving as the base material of the anti-corrosion treatment layers 14a and 14b to the following treatments: degreasing treatment, hydrothermal modification treatment, anodizing treatment, chemical conversion treatment, coating-type anti-corrosion treatment by applying a coating agent having an anti-corrosion function, or an anti-corrosion treatment obtained by combining these treatments.
[0085] Among the above-mentioned treatments, degreasing treatment, hydrothermal modification treatment, and anodizing treatment, in particular, hydrothermal modification treatment and anodizing treatment are treatments that use a treatment agent to dissolve the surface of the metal foil (aluminum foil) to form a metal compound (aluminum compound (boehmite, aluminum oxide)) with excellent corrosion resistance. Therefore, since a structure in which a co-continuous structure is formed from the metal foil layer 13 to the anti-corrosion treatment layer 14a, 14b, such treatment is sometimes also included in the definition of chemical conversion treatment.
[0086] As degreasing treatment, acid degreasing and alkali degreasing can be listed. As acid degreasing, a method of acid degreasing using the above-mentioned inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid and hydrofluoric acid alone, or using an acid obtained by mixing them can be listed. In addition, as acid degreasing, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound such as monosodium ammonium difluoride in the above-mentioned inorganic acid, not only can the degreasing effect of the metal foil layer 13 be achieved, but also a passive metal fluoride can be formed, which is effective in terms of hydrofluoric acid resistance. As alkali degreasing, a method using sodium hydroxide, etc. can be listed.
[0087] As the above-mentioned hydrothermal modification treatment, for example, boehmite treatment obtained by immersing the metal foil layer 13 in boiling water with triethanolamine can be used. As the above-mentioned anodic oxidation treatment, for example, acid-proof aluminum treatment can be used. In addition, as the above-mentioned chemical conversion treatment, for example, chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment or a combination of two or more of them can be used. These hydrothermal modification treatments, anodic oxidation treatments, and chemical conversion treatments are preferably subjected to the above-mentioned degreasing treatment in advance.
[0088] It should be noted that the chemical conversion treatment is not limited to the wet method, and for example, a method of mixing the treatment agent used in these treatments with the resin component and applying the mixture can be used. In addition, as the anti-corrosion treatment, a coating type chromate treatment is preferred from the viewpoint of maximizing its effect and treating waste liquid.
[0089] Examples of coating agents used for coating-type corrosion protection include coating agents containing at least one selected from the group consisting of rare earth element oxide sols, anionic polymers, and cationic polymers. The method using a coating agent containing a rare earth element oxide sol is particularly preferred.
[0090] The mass per unit area of the anticorrosion treatment layers 14a and 14b is preferably 0.005 to 0.200 g / m 2 In the range of 0.010 to 0.100 g / m 2 If it is 0.005g / m 2 If the above mass per unit area exceeds 0.200 g / m 2 , the anti-corrosion function is also saturated, and no further effect is expected. It should be noted that in the above content, the mass per unit area is recorded, but if the specific gravity is known, the thickness can also be converted based on the specific gravity.
[0091] From the viewpoint of the anticorrosion function and the function as an anchor, the thickness of the anticorrosion treatment layers 14 a and 14 b is, for example, preferably 10 nm to 5 μm, and more preferably 20 to 500 nm.
[0092] <Sealing layer 16>
[0093] The sealing layer 16 is a layer that imparts sealing properties to the outer packaging material 10 by heat sealing, and is a layer that is disposed inside and heat-sealed (heat-fused) when the power storage device is assembled.
[0094] Examples of the sealing layer 16 include films made of acrylic resins, polyolefin resins, or polyester resins. The sealing layer 16 is preferably a film made of polyolefin resins or polyester resins, and more preferably a film made of polyester resins, because the melting point is high and the heat resistance of the resulting packaging material is further improved.
[0095] Examples of the acrylic resin include polymethyl methacrylate resin (PMMA), etc. These acrylic resins may be used alone or in combination of two or more.
[0096] Examples of polyolefin resins include low-density, medium-density, and high-density polyethylenes, ethylene-α-olefin copolymers, polypropylene, and propylene-α-olefin copolymers. The polyolefin resin used as a copolymer may be a block copolymer or a random copolymer.
[0097] Examples of the polyester resin include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). These polyester resins may be used alone or in combination of two or more.
[0098] The sealant layer 16 may be a single-layer film or a multi-layer film, and may be selected according to the required function. When the sealant layer 16 is a multi-layer film, the layers may be laminated by coextrusion or dry lamination.
[0099] The sealing layer 16 may contain various additives such as a flame retardant, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, and a tackifier.
[0100] The thickness of the sealing layer 16 is preferably 10 to 100 μm, more preferably 20 to 60 μm. When the thickness of the sealing layer 16 is 10 μm or more, sufficient heat sealing strength can be obtained, and when the thickness is 100 μm or less, the amount of water vapor intrusion from the end of the packaging material can be reduced.
[0101] From the viewpoint of further improving heat resistance, the melting peak temperature of the sealing layer 16 is preferably 200 to 280°C.
[0102] The packaging material 10 can be used as a packaging material for a secondary battery such as a lithium-ion battery, a nickel-metal hydride battery, and a lead-acid battery, and an electrochemical capacitor such as an electric double-layer capacitor. Among them, the packaging material 10 has excellent heat resistance and excellent moisture barrier properties even in a high temperature environment, and is therefore suitable as a packaging material for an all-solid-state battery using a solid electrolyte that is intended to be used in such an environment.
[0103] As mentioned above, the preferred embodiment of the packaging material for a power storage device of this embodiment has been described in detail, but the present disclosure is not limited to the specific embodiment, and various modifications and changes can be made within the scope of the gist of the present disclosure described in the claims.
[0104] For example, in Figure 1 2 shows the case where the anti-corrosion treatment layers 14a and 14b are provided on both surfaces of the metal foil layer 13, but only one of the anti-corrosion treatment layers 14a and 14b may be provided, or no anti-corrosion treatment layer may be provided.
[0105] [Method for producing packaging material]
[0106] Next, a method for manufacturing the sealing material 10 will be described. It should be noted that the method for manufacturing the sealing material 10 is not limited to the following method.
[0107] As a method for manufacturing the sealing material 10 , for example, there can be mentioned a method of sequentially performing the following steps S11 to S13 .
[0108] Step S11 : a step of forming the anti-corrosion treatment layer 14 a on one surface of the metal foil layer 13 and forming the anti-corrosion treatment layer 14 b on the other surface of the metal foil layer 13 .
[0109] Step S12 : a step of bonding the surface of the anticorrosion treated layer 14 a opposite to the metal foil layer 13 to the base material layer 11 via the first adhesive layer 12 .
[0110] Step S13 : a step of forming a sealing layer 16 on the surface of the anticorrosion treated layer 14 b on the opposite side to the metal foil layer 13 via the second adhesive layer 15 .
[0111] <Step S11>
[0112] In step S11, an anti-corrosion treatment layer 14a is formed on one surface of the metal foil layer 13, and an anti-corrosion treatment layer 14b is formed on the other surface of the metal foil layer 13. The anti-corrosion treatment layers 14a and 14b can be formed separately, or both can be formed at one time. Specifically, for example, by applying an anti-corrosion treatment agent (the base material of the anti-corrosion treatment layer) on both surfaces of the metal foil layer 13, and then drying, curing, and baking (baking) in sequence, the anti-corrosion treatment layers 14a and 14b are formed at one time. In addition, an anti-corrosion treatment agent can also be applied on one surface of the metal foil layer 13, and dried, cured, and baked in sequence to form the anti-corrosion treatment layer 14a, and then the anti-corrosion treatment layer 14b is similarly formed on the other surface of the metal foil layer 13. The formation order of the anti-corrosion treatment layers 14a and 14b is not particularly limited. In addition, different anti-corrosion treatment agents can be used in the anti-corrosion treatment layer 14a and the anti-corrosion treatment layer 14b, or the same anti-corrosion treatment agent can be used. The method for applying the anticorrosion agent is not particularly limited, and for example, gravure coating, gravure reverse coating, roll coating, reverse roll coating, die coating, rod coating, kiss coating, comma coating, small-diameter gravure coating, etc. can be used.
[0113] <Step S12>
[0114] In step S12, the surface of the anti-corrosion treatment layer 14a opposite to the metal foil layer 13 is adhered to the base material layer 11 by dry lamination or the like using an adhesive forming the first adhesive layer 12. In step S12, a heat treatment may be performed to promote the adhesion of the first adhesive layer 12. From the viewpoint of the excellent resistance to molding curling of the packaging material, the temperature during the heat treatment is preferably 140° C. or less.
[0115] <Step S13>
[0116] After step S12, the surface of the anticorrosion treatment layer 14b on the opposite side of the metal foil layer 13 of the laminated body in which the base material layer 11, the first adhesive layer 12, the anticorrosion treatment layer 14a, the metal foil layer 13 and the anticorrosion treatment layer 14b are sequentially laminated is adhered to the sealing layer 16 by dry lamination or the like using an adhesive for forming the second adhesive layer 15. In step S13, in order to promote the adhesion of the second adhesive layer 15, a heat treatment may also be performed. In view of the excellent resistance to molding curling of the packaging material, the temperature during the heat treatment is preferably 140°C or less, and more preferably 120°C or less.
[0117] Through the above-described steps S11 to S13, the encapsulating material 10 is obtained. It should be noted that the order of the steps in the method for manufacturing the encapsulating material 10 is not limited to the method of sequentially performing the above-described steps S11 to S13. For example, the order of the steps performed may be appropriately changed by performing step S11 after performing step S12.
[0118] [Electricity storage device]
[0119] Figure 3 FIG. 1 is a perspective view showing an embodiment of a power storage device manufactured using the above-mentioned packaging material. Figure 3 As shown in FIG. 1 , the power storage device 50 includes the following components: a battery element (power storage device body) 52 including electrodes, two metal terminals (leads, current output terminals) 53 extending from the electrodes and used to output current from the battery element 52 to the outside, and a packaging material 10 that contains the battery element 52 in an airtight state. The packaging material 10 is the packaging material 10 involved in the present embodiment described above, and is used as a container for accommodating the battery element 52. In the packaging material 10, the base material layer 11 is the outermost layer, and the sealing layer 16 is the innermost layer. That is, the packaging material 10 is configured as follows: a laminate film is folded in half and the peripheral portion is heat-fused, or two laminate films are overlapped and the peripheral portions are heat-fused, so that the base material layer 11 is the outer side of the power storage device 50 and the sealing layer 16 is the inner side of the power storage device 50, thereby containing the battery element 52 inside. The metal terminal 53 is sandwiched and sealed by the packaging material 10 that forms a container with the sealing layer 16 as the inner side. The metal terminal 53 may also be clamped by the packaging material 10 via the tab seal.
[0120] The battery element 52 is formed by interposing an electrolyte between a positive electrode and a negative electrode. The metal terminal 53 is formed by taking a part of the current collector out of the packaging material 10, and is made of metal foil such as copper foil and aluminum foil.
[0121] The power storage device 50 of this embodiment may be an all-solid-state battery. In this case, a solid electrolyte such as a sulfide-based solid electrolyte is used as the electrolyte of the battery element 52. Since the power storage device 50 of this embodiment uses the packaging material 10 of this embodiment, even when used in a high temperature environment (e.g., 150° C.), excellent lamination strength, sealing strength, and moisture barrier properties can be ensured.
[0122] Example
[0123] Hereinafter, the present disclosure will be specifically described based on examples, but the present disclosure is not limited thereto.
[0124] <Base layer (thickness 25 μm)>
[0125] A polyethylene terephthalate film having one surface subjected to corona treatment was used.
[0126] <First Adhesive Layer (Thickness 4 μm)>
[0127] As the material for the first adhesive layer, a urethane resin (manufactured by Mitsui Chemicals, trade name "main agent: Takelac A-515 (solid content concentration 50 mass%), curing agent: Takenate D-140 (solid content concentration 74 mass%)" was prepared. These materials were mixed in a ratio of 30 mass parts of curing agent to 100 mass parts of main agent, and a material diluted with ethyl acetate to a solid content concentration of 30 mass% was used as an adhesive.
[0128] <First Anticorrosion Treatment Layer (Base Layer Side) and Second Anticorrosion Treatment Layer (Sealing Layer Side)
[0129] (CL-1): A "sodium polyphosphate-stabilized cerium oxide sol" having a solid content concentration adjusted to 10% by mass using distilled water as a solvent was used. The sodium polyphosphate-stabilized cerium oxide sol was obtained by mixing 10 parts by mass of sodium phosphate with respect to 100 parts by mass of cerium oxide.
[0130] (CL-2): A composition consisting of 90% by mass of "polyallylamine (manufactured by Nittobo Co., Ltd.)" whose solid content concentration was adjusted to 5% by mass using distilled water as a solvent and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corp.)" was used.
[0131] <Second Adhesive Layer (Thickness 3 μm)>
[0132] An adhesive was used in which the main agent, the polyfunctional isocyanate compound and the carbodiimide described in Table 1 were mixed at the ratios shown in Table 1. Toluene was appropriately mixed in the adhesive so that the nonvolatile component became 15% by mass. The details of the main agent, the polyfunctional isocyanate compound and the carbodiimide described in Table 1 are as follows.
[0133] {Main agent}
[0134] Acid-modified polyolefin (ratio of non-volatile components: 30 mass %, hydroxyl value: 40 KOHmg / g, manufactured by Riken Vitamin Co., Ltd., grade name: "Rikeaid MG-400EM")
[0135] Polyacrylic acid polyol (ratio of non-volatile components: 50 mass %, hydroxyl value: 10 to 20 KOH mg / g, functional group equivalent: 5610 g / mol, manufactured by MITSUBISHI RAYON CO., LTD., grade name: "LR209")
[0136] {Polyfunctional isocyanate compound}
[0137] HDI series (hexamethylene diisocyanate-adduct, non-volatile content: 50 mass%, NCO content: 18.7 mass%, functional group equivalent: 225 g / mol, manufactured by Asahi Kasei Corporation, grade name: "E402-80B")
[0138] TDI series (toluene diisocyanate-adduct, non-volatile content: 50 mass%, NCO content: 17.7 mass%, functional group equivalent: 237 g / mol, manufactured by Nippon Polyurethane Industry Co., Ltd., grade name: "Coronate L")
[0139] IPDI series (isophorone diisocyanate-adduct, non-volatile content: 74.6 mass%, NCO content: 10.3 mass%, functional group equivalent: 408 g / mol, manufactured by Mitsui Chemicals, Inc., grade name: "D-140N")
[0140] {Carbodiimide}
[0141] As carbodiimide, “V-07” (grade name, nonvolatile content: 50% by mass) manufactured by Nisshinbo Chemical Inc. was used.
[0142] <Metal foil layer (thickness 35μm)>
[0143] A soft aluminum foil ("8079 material" manufactured by Toyo Aluminum KK) that had been subjected to an annealing and degreasing treatment was prepared.
[0144] <Sealing layer (thickness 40 to 70 μm)>
[0145] The materials used are those listed in Table 1. The details of the materials listed in Table 1 are as follows.
[0146] ·Acrylic resin film (manufactured by Okura Industries, trade name "OXIS-PMMA")
[0147] ·Polyester film (manufactured by Toyobo Co., Ltd., trade name "Olyester DE046")
[0148] PP film (polypropylene film, manufactured by Idemitsu Kosan Co., Ltd., trade name "Unilax RT-680CA")
[0149] [Manufacture of packaging materials]
[0150] <Examples 1 to 5 and Comparative Examples 1 to 3>
[0151] The metal foil layer was adhered to the base material layer using an adhesive (first adhesive layer) by dry lamination, and aged at 80° C. for 120 hours. Next, the sealant layer was adhered to the surface of the metal foil layer opposite to the surface adhered to the first adhesive layer by dry lamination using an adhesive (second adhesive layer), and aged at 60° C. for 120 hours.
[0152] The laminated body obtained in this way was subjected to heat treatment to produce a packaging material (base material layer / first adhesive layer / metal foil layer / second adhesive layer / sealing layer).
[0153] <Examples 6 to 9>
[0154] First, the first and second anticorrosion treatment layers were provided on the metal foil layer according to the following steps. That is, micro gravure coating was performed so that the dry coating amount became 70 mg / m 2 (CL-1) was applied on both sides of the metal foil layer in a manner of 1:1 and baked in a drying unit at 200°C. Then, micro-gravure coating was performed so that the dry coating amount became 20 mg / m 2 (CL-2) is applied on the obtained layer in a manner to form a composite layer composed of (CL-1) and (CL-2) as the first and second anti-corrosion treatment layers. The composite layer exhibits anti-corrosion performance by combining (CL-1) and (CL-2).
[0155] A packaging material (base material layer / first adhesive layer / first anti-corrosion layer / metal foil layer / second anti-corrosion layer / second adhesive layer / sealing layer) was manufactured in the same manner as in Example 1, except that the metal foil layer provided with the first and second anti-corrosion layers was used.
[0156] [Evaluation of packaging materials]
[0157] <Examples 1 to 9 and Comparative Examples 1 and 2>
[0158] {Determination of infrared absorption spectrum peak}
[0159] The packaging material is cut and peeled off between the sealing layer and the metal foil layer, or between the sealing layer and the anti-corrosion treatment layer. The infrared absorption spectrum peak of the outermost surface of the second adhesive layer exposed by peeling is measured by attenuated total reflection (ATR) of Fourier transform infrared (FT-IR) spectroscopy. X defined by the following formula (2) is calculated based on the intensity of the infrared absorption spectrum peak. The results are shown in Table 2.
[0160] X={(C+D)-B} / A…(2)
[0161] [wherein, A to D are the intensities of the infrared absorption spectrum of the second adhesive layer measured by infrared spectroscopy, and A represents the wave number 3040 to 2760 cm -1 The maximum intensity, B represents the wave number 1850~1780cm -1 The maximum intensity, C represents the wave number 1760~1600cm -1 The maximum intensity, D represents the wave number 2150~2090cm -1 Maximum strength.]
[0162] The details of the measuring apparatus and conditions are as follows.
[0163] (Measurement apparatus and conditions)
[0164] Measuring device: Spectrum Spotlight 400 (trade name, manufactured by PerkinElmer)
[0165] Prism: Germanium
[0166] Wave number resolution: 4cm -1
[0167] Cumulative times: 4 times
[0168] Baseline: wave number 2400~2600cm -1 The straight line between
[0169] [Evaluation of lamination strength]
[0170] (Lamination strength at 80°C)
[0171] The packaging material cut into 15 mm width was placed in a high temperature environment of 80°C for 5 minutes. Then, using a tensile testing machine (manufactured by Shimadzu Corporation), the lamination strength between the metal foil layer and the sealing layer of the packaging material in an environment of 80°C was measured by a 90-degree peel test at a tensile speed of 50 mm / min. In addition, based on the obtained lamination strength, evaluation was performed according to the following criteria. The results are shown in Table 2.
[0172] A: Lamination strength is 2.5N / 15mm or more
[0173] B: Lamination strength is 2.0N / 15mm or more and less than 2.5mm
[0174] C: Lamination strength is 1.5N / 15mm or more and less than 2.0mm
[0175] D: Lamination strength is less than 1.5N / 15mm
[0176] (Lamination strength at 150°C)
[0177] The lamination strength under 150°C was evaluated in the same manner as the lamination strength under 80°C except that the temperature for placing the packaging material was 150°C and the temperature for performing the 90°C peel test was 150°C. The results are shown in Table 2.
[0178] (Laminate Strength after Hydrogen Sulfide Exposure)
[0179] The packaging material cut into 15 mm width was placed in an environment with a hydrogen sulfide concentration of 20 ppm and 100°C for 1 week. Then, the lamination strength between the metal foil layer and the sealing layer of the packaging material in an environment of 150°C was measured by a 90-degree peel test at a tensile speed of 50 mm / min using a tensile tester (manufactured by Shimadzu Corporation). The obtained lamination strength was evaluated based on the same criteria as the lamination strength in an environment of 80°C. The results are shown in Table 2.
[0180] [Evaluation of heat seal strength]
[0181] The packaging material was cut into a size of 120 mm × 60 mm and folded in half so that the sealing layer was on the inside. Next, the end on the opposite side of the folded part was heat-sealed to a width of 10 mm at 220°C / 0.5 MPa / 3 seconds and kept at room temperature for 6 hours. Then, the central part of the heat-sealed part in the longitudinal direction was cut out with a width of 15 mm × a length of 300 mm to prepare a sample for measuring the heat seal strength. The sample was placed in a test environment at 150°C for 5 minutes, and then a tensile tester (manufactured by Shimadzu Corporation) was used to perform a T-peel test on the heat-sealed part of the sample at a tensile speed of 50 mm / min. Then, based on the obtained heat seal strength, an evaluation was performed according to the following criteria. The results are shown in Table 2.
[0182] A: Heat seal strength is 15N / 15mm or more
[0183] B: Heat seal strength is 10N / 15mm or more and less than 15N / 15mm
[0184] C: Heat seal strength is 5N / 15mm or more and less than 10N / 15mm
[0185] D: Heat seal strength is less than 5N / 15mm
[0186] [Evaluation of moisture barrier properties]
[0187] The 120mm×110mm packaging material was overlapped in a way that the sealing layers were facing each other and folded into an outer dimension of 120mm×55mm. Next, the end edges on both sides were heat-sealed to 10mm width at 220℃ / 0.5MPa / 3 seconds to make a bag with one side open. Then, 3mL of dehydrated ethylene glycol was injected into the content, and the remaining side was heat-sealed with a width of 3mm. It should be noted that the 10mm wide sealed portion is considered to have almost no moisture permeation, and the 3mm sealed portion was taken as the measurement object. The manufactured battery container was stored in an environment of 120℃ and 90%RH for 4 weeks, and the moisture content contained in the ethylene glycol after storage was measured by the Karl Fischer method to measure the moisture permeability. Based on the obtained moisture permeability, evaluation was performed according to the following criteria. The results are shown in Table 2.
[0188] A: Water permeability is below 250ppm
[0189] B: Moisture permeability is more than 250ppm and less than 300ppm
[0190] C: Water permeability is more than 300ppm and less than 350ppm
[0191] D: Water permeability exceeds 350ppm
[0192] [Comprehensive evaluation]
[0193] The packaging materials were comprehensively evaluated according to the following criteria. The total value of each evaluation is the total value when the evaluation criteria "A", "B", "C" and "D" for the evaluation of lamination strength, heat seal strength and moisture barrier properties are set to 3 points, 2 points, 1 point and 0 points respectively. The results are shown in Table 2.
[0194] A: When the total value of each evaluation is 13 points or more.
[0195] B: The total of all evaluations is 9 points or more and 12 points or less. However, cases with one D grade are excluded.
[0196] C: The total of all evaluations is 5 points or more and 8 points or less. However, cases with 1 D grade are excluded.
[0197] D: There are 1 or more D grades in each evaluation
[0198] [Table 1]
[0199]
[0200] [Table 2]
[0201]
[0202] The gist of the present disclosure is as follows [1] to [9].
[0203] [1] A packaging material for a power storage device, the packaging material having a laminated structure including the following layers in order:
[0204] Base material layer,
[0205] The first bonding layer,
[0206] Metal foil layer,
[0207] a second adhesive layer, and
[0208] Sealing layer,
[0209] The second adhesive layer comprises at least a reaction product of an acid-modified polyolefin and a multifunctional isocyanate compound,
[0210] The second adhesive layer satisfies the condition represented by the following inequality (1):
[0211] 0.01≤{(C+D)-B} / A≤0.60…(1)
[0212] [wherein, A to D are the intensities of the infrared absorption spectrum of the second adhesive layer measured by infrared spectroscopy, and A represents the wave number 3040 to 2760 cm -1 The maximum intensity, B represents the wave number 1850~1780cm -1 The maximum intensity, C represents the wave number 1760~1600cm -1 The maximum intensity, D represents the wave number 2150~2090cm -1 Maximum strength.]
[0213] [2] The packaging material according to [1], wherein the polyfunctional isocyanate compound contains at least one selected from the group consisting of polymers of aliphatic polyfunctional isocyanate compounds and polymers of polyfunctional isocyanate compounds containing an aromatic ring.
[0214] [3] The packaging material according to [1] or [2], wherein one or both of the layers between the first adhesive layer and the metal foil layer and between the second adhesive layer and the metal foil layer include an anti-corrosion treatment layer.
[0215] [4] The packaging material according to any one of [1] to [3], wherein the sealing layer comprises at least one of a polyolefin-based resin and a polyester-based resin.
[0216] [5] The packaging material according to any one of [1] to [4], wherein at least one of the first adhesive layer and the second adhesive layer contains a hydrogen sulfide adsorbing substance.
[0217] [6] The packaging material according to any one of [1] to [5], wherein the second adhesive layer further contains a carbodiimide compound.
[0218] [7]. The packaging material according to any one of [1] to [6], which is for solid-state batteries.
[0219] [8] A power storage device comprising:
[0220] Power storage device body,
[0221] A current output terminal extending from the power storage device body, and
[0222] The packaging material described in any one of [1] to [7] that holds the current output terminal and accommodates the main body of the power storage device.
[0223] [9] The power storage device according to [8], which is an all-solid-state battery.
[0224] Explanation of symbols
[0225] 10…packaging material (packaging material for power storage device), 11…base material layer (outer layer), 12…first adhesive layer, 13…metal foil layer, 14a, 14b…anti-corrosion treatment layer, 15…second adhesive layer, 16…sealing layer, 50…power storage device.
Claims
1. A packaging material for a power storage device, having a laminated structure comprising the following layers in sequence: Base material layer, The first bonding layer, Metal foil layer, a second adhesive layer, and Sealing layer, The second adhesive layer at least comprises a reaction product of an acid-modified polyolefin and a multifunctional isocyanate compound. The second adhesive layer satisfies the condition represented by the following inequality (1): 0.01≤{(C+D)-B} / A≤0.60…(1) Wherein, A to D are the intensities of the infrared absorption spectrum of the second adhesive layer measured by infrared spectroscopy, and A represents the wave number 3040 to 2760 cm -1 The maximum intensity, B represents the wave number 1850~1780cm -1 The maximum intensity, C represents the wave number 1760~1600cm -1 The maximum intensity, D represents the wave number 2150~2090cm -1 Maximum strength.
2. The packaging material according to claim 1, wherein: The polyfunctional isocyanate compound includes at least one selected from the group consisting of polymers of aliphatic polyfunctional isocyanate compounds and polymers of polyfunctional isocyanate compounds containing an aromatic ring.
3. The packaging material according to claim 1 or 2, wherein: An anti-corrosion treatment layer is provided between one or both of the first adhesive layer and the metal foil layer and between the second adhesive layer and the metal foil layer.
4. The packaging material according to any one of claims 1 to 3, wherein: The sealant layer includes at least one of a polyolefin-based resin and a polyester-based resin.
5. The packaging material according to any one of claims 1 to 4, wherein: At least one of the first adhesive layer and the second adhesive layer contains a hydrogen sulfide adsorbing substance.
6. The packaging material according to any one of claims 1 to 5, wherein: The second adhesive layer further contains a carbodiimide compound.
7. The packaging material according to any one of claims 1 to 6, which is for all-solid-state batteries.
8. An electric storage device comprising: Power storage device body, a current output terminal extending from the power storage device body, and The packaging material according to any one of claims 1 to 7, which sandwiches the current output terminal and accommodates the power storage device body. 9 . The power storage device according to claim 8 , which is an all-solid-state battery.
Citation Information
Patent Citations
External facing material for power storage device
JP2013101765A
